Pity the Finance Minister : Issues in Managing a Substantial Scaling-Up of Aid Flows - Heller, Peter (IMF Working Papers; Working Paper ;, 2005)
Substantially scaling up of aid flows will require development partners to address many issues, including the impact of higher aid flows on: the competitiveness of aid recipients; the management of fiscal and monetary policy; the delivery of public services; behavioral incentives; and the rate of growth of the economy. Other issues will include the appropriate sequencing of aid-financed investments; balancing alternative expenditure priorities; the implications for fiscal and budget sustainability; and exit strategies from donor funding. Donors will need to ensure greater long-term predictability and reduced short-term volatility of aid. The international financial institutions can play a critical role in helping countries address these scaling-up issues.